Condorcet's jury theorem as a rational justification of soft paternalistic consumer policies - Malte Dold (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2015)
The objective of this note is to revisit the meaningfulness of the Condorcet Jury Theorem (CJT) and apply it to the recent debate on liberal paternalism and consumer protection. The CJT con-sists of two parts, (a) stating that a jury of experts is always more competent than a single expert given a certain level of competence, and (b) asserting that for large juries, the collective com-petence approaches infallibility. This note argues that these insights suggest the application of a Condorcet jury voting procedure to the case of nudging boundedly rational consumers. The note proposes a simple calculus for finding an optimal jury size and advocates consumers' meta-preferences as the jury's evaluative dimension for designing soft paternalistic policies.
Keywords: B41; D03; D63; D71; 330; Bounded Rationality; Condorcet Jury Theorem; Consumer Policy; Educative Nudges; Hierarchical Preferences; Knowledge Problem; Liberal Paternalism